Salivary glucose estimation: A noninvasive method - Harshada Ragunathan; Nalini Aswath; T Sarumathi (Wolters Kluwer Medknow Publications, 2019)
Background: There is an alarming rise in number of people with diabetes mellitus over these years. Oral physicians are more liable to come in contact with a significant number of patients with diabetes mellitus. Due to the lack of early diagnosis and treatment, diabetes is a major cause of death worldwide. While the early diagnosis of diabetes is essential to prevent its complication, the most commonly used diagnostic method is by the detection of glucose level in blood, but the sample collection is invasive and painful. Thus, there arises a need for a noninvasive and painless technique to detect glucose levels. The aim of this study is to estimate the glucose levels in saliva and correlate it with serum glucose. Materials and Methods: The study was conducted in the Outpatient Department of Oral Medicine and Radiology. Forty patients' serum and saliva were collected and the levels were estimated using the glucose oxidase-peroxidasemethod. Results: Data obtained was subjected to statistical analysis using t-test. Highly significant P value (P = 0.00) was obtained between the serum blood glucose and salivary glucose level. A distinct difference was observed in the salivary glucose between the control and diabetic group. Conclusion: Diabetes mellitus is a globally widespread disease. As the salivary collection is easy and noninvasive, in this study, an attempt has been made to diagnose diabetes mellitus by estimating the salivary glucose level in comparison with serum blood glucose level.